Pengembangan Alat Permainan Edukatif Magic Bag Untuk Meningkatkan Kemampuan Kognitif Anak Usia Dini - Mey Tia Nur Hidayah; Nurlaili Dina Hafni (Alzam: Journal of Islamic Early Childhood Education, 2024)
Background This research does not get a less creative stimulus because it relies on textbooks as learning media. This study aims to determine the validity, practicality and effectiveness of Magic Bag educative games to improve cognitive abilities in students in Kindergarten Dharma Wanita XXII Parengan Academic Year 2023/2024. This study uses the development research method or R&D (Research and Development) with the 4D model. The validity test was carried out by the validator of media experts, material experts, tutors, and also from users. While data collection uses observations, questionnaires, and documentation. Based on data from the validity test, the Magic Bag educational game tool meets the very valid or very feasible category. And feasibility validation is obtained from material expert data with a percentage of 86% and for the validation of the feasibility of data on media experts get a percentage of 93.3%. The average validation results received a percentage of 89.6%. Through the calculation of the percentage of educational game tools Magic Bag is stated to be very valid or very suitable for use in the learning process. Based on the practicality level of the Magic Bag Educative Games, the questionnaire is obtained from the student response, the percentage of 94.3% with the very good category and obtained from the Teacher's Response Questionnaire Sheet gets a percentage of 96.6% with a very good category while the level of effectiveness of the media tool media Educative Magic Bag gets a N-gain value of 0.7 with a high category and an average of 86.6%. It can be concluded that the media of Magic Bag educational game tools is effectively used in the learning process.